2019
DOI: 10.17554/j.issn.2224-3992.2019.08.819
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D Replacement on Liver Enzymes in Patients with Non-alcoholic Fatty Liver Disease

Abstract: BACKGROUND AND AIMS: The relationship between vitamin D-deficiency and pathogenesis of non-alcoholic fatty liver diseases (NAFLD) has been always a controversial subject. The present study is aimed to investigate the effects of vitamin D on the reduction of liver enzymes and, then, compare its effects with those of diet and physical activities individually. PATIENTS AND METHODS: The present double-blinded randomized clinical trial was conducted at …..University of Medical Sciences in 2017. For this purpose, 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…After title and abstract screening, 48 articles remained and after full-text review, 32 articles were excluded from the current study for different reasons. Thus, the final systematic review and meta-analysis was done on 16 papers ( Table 1 ) ( Sharifi et al, 2014 ; Foroughi et al, 2015 ; Barchetta et al, 2016 ; Foroughi et al, 2016 ; Nadjarzadeh et al, 2016 ; Sharifi et al, 2016 ; Lorvand Amiri et al, 2017 ; Sakpal et al, 2017 ; Dabbaghmanesh et al, 2018 ; Geier et al, 2018 ; Mansourian Hosseini et al, 2018 ; MOUODI et al, 2018 ; Hajiaghamohammadi et al, 2019 ; Hussain et al, 2019 ; Shidfar et al, 2019 ; Foroughi et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After title and abstract screening, 48 articles remained and after full-text review, 32 articles were excluded from the current study for different reasons. Thus, the final systematic review and meta-analysis was done on 16 papers ( Table 1 ) ( Sharifi et al, 2014 ; Foroughi et al, 2015 ; Barchetta et al, 2016 ; Foroughi et al, 2016 ; Nadjarzadeh et al, 2016 ; Sharifi et al, 2016 ; Lorvand Amiri et al, 2017 ; Sakpal et al, 2017 ; Dabbaghmanesh et al, 2018 ; Geier et al, 2018 ; Mansourian Hosseini et al, 2018 ; MOUODI et al, 2018 ; Hajiaghamohammadi et al, 2019 ; Hussain et al, 2019 ; Shidfar et al, 2019 ; Foroughi et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis indicated that supplementation with vitamin D significantly increased LDL-C and had not significant effect on TG and HDL-C in patients with CVDs ( Wang et al, 2012 ). One study found that vitamin D supplementation reduced LDL-C but no significant change was found on HDL-C ( Hajiaghamohammadi et al, 2019 ). In another study supplementation with vitamin D3 as 50,000 IU per week for 12 weeks in NAFLD had no significant effect on lipid profile and body composition ( Hussain et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since vitamin 'D' has anti-inflammatory properties, it has been proposed that it may act as an 'immune-modulator' to reduce inflammation and suppress both fibroblast proliferation and collagen production in the liver and also improve oxidative stress and prevent cellular damage in patients with NASH. Accordingly, vitamin 'D' supplementation may improve liver inflammation and decrease enzymes [32,36,37].…”
Section: Discussionmentioning
confidence: 99%